Bilge System Design on 500 GT Ferry for Bulukumba–Selayar Route. Issue 1 (November 2021) - Pawara, M U; Setiawan, W; Ikhwani, R J; Alamsyah,; Wulandari, A I; Suardi,; Nugraha A, A M; Hidayat, T; Ansori, M I; Mahmuddin, F
Abstract: A piping system is the main part of a system that connects the point where the fluid is stored to the point of accessing the pipe. Both pipe strength and pump capacity must be carefully considered because the safety of a ship will depend on the piping arrangement as well as on other ship equipment. The main function of the bilge pipe system is the drainage system in case of flooding in the compartment due to grounding or collision. Another function is the drainage system in the event of leaks on the welding root, condensation on the side shell leaks on the piping system (particularly in the engine room), and discharge water due to water-splash over the hatch. This study aimed to design a bilge piping system design using Autopipe Software with ASME B31.3 standard for the piping process. The design phase of the system is collecting data, then determining the load case. After that, selecting components needed for the construction of the system. The following step, making 3-dimensional modeling on Autopipe by entering input based on the determining components. Finally, validating the model, and proceed with the running model according to the specified load case. The result of the running model is the pipe stress level which is described in the stress code in the Autopipe. The final results are 3-dimensional drawings of the system and the number of components needed for constructing the system under Indonesian Classification Bureau (BKI) rules and ASME B31.3 standards for the piping process.